2017
DOI: 10.1038/s41598-017-00969-0
|View full text |Cite|
|
Sign up to set email alerts
|

Fish oil, lard and soybean oil differentially shape gut microbiota of middle-aged rats

Abstract: High-fat diets have been associated with overweight/obesity and increased mortality in middle-aged populations. However, it is still unclear how gut microbiota in middle-aged populations responds to dietary fats at a normal dose. In this study, we explored gut microbiota structure in middle-aged rats (aged 12 months) after feeding 4% (w/w) soybean oil, lard or fish oil for 3 months, respectively. The results showed that the gut microbiota structure in the fish oil group was substantially different from those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 61 publications
3
33
1
Order By: Relevance
“…One study in mice fed a lard-containing diet reported an increase in the abundance of Bacteroides, Turicibactor, and Bilophila, while mice consuming a fish oil-based diet were enriched for Bifidobacterium, Adlercreutzia, Lactobacillus, Streptococcus, and Akkermansia muciniphila (Caesar et al, 2015). In contrast, another study on rats reported an increase in Akkermansia in response to intake of a lardcontaining diet, while intake of a fish oil-containing diet was associated with a higher abundance of Desulfovibrio, Bilophila, Desulfovibrio, and Helicobacter (Li et al, 2017). The different results may relate to differences in study designs, e.g., different rodent species, sample handling, 16S…”
Section: Effect Of Lipids On the Microbiotamentioning
confidence: 92%
See 1 more Smart Citation
“…One study in mice fed a lard-containing diet reported an increase in the abundance of Bacteroides, Turicibactor, and Bilophila, while mice consuming a fish oil-based diet were enriched for Bifidobacterium, Adlercreutzia, Lactobacillus, Streptococcus, and Akkermansia muciniphila (Caesar et al, 2015). In contrast, another study on rats reported an increase in Akkermansia in response to intake of a lardcontaining diet, while intake of a fish oil-containing diet was associated with a higher abundance of Desulfovibrio, Bilophila, Desulfovibrio, and Helicobacter (Li et al, 2017). The different results may relate to differences in study designs, e.g., different rodent species, sample handling, 16S…”
Section: Effect Of Lipids On the Microbiotamentioning
confidence: 92%
“…Few dietary intervention studies have focused exclusively on modulating the type of dietary fat source. Still, the dietary lipid origin has been shown to impact both on the composition and diversity of the cecal and colonic microbiota in rodents (Caesar et al, 2015;Huang et al, 2013;Li et al, 2017;Patterson et al, 2014;Robertson et al, 2017), driving associations in humans between certain bacterial taxa and different dietary fats (Wu et al, 2011). In the few studies conducted in rodents, the effect of fat source on bacterial taxa differs somewhat between studies.…”
Section: Effect Of Lipids On the Microbiotamentioning
confidence: 99%
“…The ability of the gut microbiome to influence host health and metabolism has become well-established in recent years. Recent studies have established an association between the gut microbiome and blood lipids in humans, mice, and rats [5,6]. Different food types can alter the host gut microbiome, including types of dietary lipids [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[12] The change in the abundance of Desulfovibrio induced by ω-3 PUFAs remains debated. One study [13] showed a decrease in Bilophila, while another [14] observed an increase in Proteobacteria, although further investigation is needed to validate these results.…”
Section: Introductionmentioning
confidence: 99%